Men, Women, and Politeness - Mytha Candria; Sulistya Ningtyas; Retno Wulandari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
The article suggests that there is no straightforward correlation between men, women, and politeness. Women do not necessarily speak more politely than men, nor do men invariably speak more rudely than women. Indeed, the binary division of male and female has frequently been challenged in contemporary scholarship, as such oppositions risk excluding and discriminating against individuals who do not culturally or socially fit into either category. Moreover, politeness is not determined by gender alone; rather it is shaped by a constellation of social factors, including culture, age, social status, race, ethnicity, and educational background.